Implementasi Strategi Pertahanan Laut Nusantara Dalam Rangka Deteksi Dini Pelanggaran Di Pesisir Garut Jawa Barat Guna Mendukung Pertahanan Negara Di Laut - Sari Putri, Puja; Ansori , Ansori; Rudiawan, Beni; Syahtaria, M. Ikhwan; Lukman Y. P (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Indonesia, with its vast maritime territory and abundant water resources, requires substantial efforts to safeguard defense and security. The effective defense strategy of the Indonesian Navy (TNI AL) involves strategically placing naval bases throughout the entire region, demonstrating a deterrent effect to potential adversaries and affirming the presence of TNI AL in the waters of the Republic of Indonesia. The aim of this research is to analyze the implementation of the Maritime Defense Strategy in early detection of threats along the coast of Garut, West Java. This qualitative research adopts a phenomenological approach, utilizing interview, observation, and documentation methods. The findings indicate that the placement of Binpotmar personnel in Cikelet Garut under the jurisdiction of Posal Pangandaran plays a crucial role in responding to the dynamics of local maritime issues. The flexibility and responsibility of Binpotmar demonstrate vital adaptability in responding to incidents at the border. Functioning as the forefront of intelligence and executing maritime operations, the presence of Binpotmar is a strategic step to enhance self-reliance in carrying out operational tasks. The research also emphasizes the optimal utilization of Cikelet Garut's potential, including the well-maintained Dutch legacy docks, through infrastructural improvements and advanced technology. The naval facility in the area can effectively respond to maritime threats, fulfill the 5R criteria in the Southern Region of Java Island, and create a deterrent effect against adversaries. The importance of collaboration with the Garut Regency Government through forkopimda is highlighted as a crucial consideration for TNI AL. Overall, the research underscores the significance of a comprehensive and collaborative approach in maintaining maritime defense and security in the region.